Nanopartículas de TiO2 : caracterização da morfologia e sua influência na cinética de sorção de hidrogênio do MgH2 - Pereira, Anderson de Farias. (2018)
Recent studies suggest that the addition of TiO2-based nanomaterials with 1D morphology to MgH2 improves significantly its hydrogen sorption properties, making it more promissing as a hydrogen storage material for mobile applications. In the present study the catalytic role of TiO2 nanorods and nanoparticles – produced by heat treatment of titanate nanotubes at 550°C (NR550), 650°C (NR650) and 750°C (NR750) – on the sorption kinetics of MgH2 was evaluated. For this, MgH2-TiO2 nanocomposites with 5wt% of additives mixed at 300rpm (NR550, NR650 and NR750) and at 100rpm (NR550/100) in a planetary ball milling were prepared. The samples were characterized by means of X-ray diffraction (XRD), BET surface area evaluation (for the additives) and Transmission Electron Microscopy (TEM) by the association of Bright and Dark Field images for the characterization of nanoparticles’ size and morphology as well as its dispersion within the composite. The sorption kinetics properties were evaluated in a Sievert’s apparatus. The results indicated that catalysts NR550 and NR650 consisted on mixture of nanorods and nanoparticles, with mean particle’s size about 34nm and NR750 consisted on nanoparticles of TiO2-anatase with small amount of rutile and mean particle’s size about 70nm. It was observed that all additives had positive effect on the sorption kinetics of MgH2, but the samples with NR750/300 (anatase and rutile nanoparticles) and NR550/300 presented the best performances, suggesting the positive effect of the presence of rutile and of anatase nanorods, respectively, on the sorption properties of the material. The reduction of milling energy apparently did not have a positive effect on the sorption kinetics of MgH2.